Vietnam geographical exploitation under the United Nations Convention on the Law of the Sea in 1982 (UNCLOS 1982) - Phach, Phung Van; Chinh, Huynh Minh; Thang, Do Chien; Tuan, Tran Anh; Nam, Phan Tuan; Anh, Le Tuan; Hoang, Cu Minh; Bach, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
As an active member of the United Nations Convention on the Law of the Sea - UNCLOS, Vietnam has completed 3 Reports on the Limits of the Continental Shelf and has submitted two of them to the Commission on the Limits of the Continental Shelf - CLCS, before the deadline 13-5-2009. Those are: (1) Outer Limits of the Vietnam’s Extended Continental Shelf: North Area (VNM-N); (2) Outer Limits of the Vietnam’s Extended Continental Shelf: Middle Area (VNM-M) and (3) Vietnam - Malaysia Joint Continental Shelf Submission. The VNM-M has not yet been submitted but it was mentioned to the CLCS and will be submitted in the appropriate time.Vietnam’s submissions were highly appreciated by CLCS; although the CLCS has not yet organized a special sub-committee to look at our reports, the secretariat of CLCS has already posted the executive reports of our submissions, with our principle claims on the continental shelf, on the website of the CLCS since May 2009. This paper presents shortly the UNCLOS and its application in Vietnam case.